Perencanaan Jaringan LTE TDD (Time Division Duplex) 2300 MHz Di Kota Pekanbaru - Rozy Syaputra; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Technological developments, especially in the field of information and telecommunications are grew rapidly. Thus the consumer needs high mobility and able to support services such as VoIP, video conference, upload/download, etc. Therefore, it needs mobile communication services to support the needs of consumers with optimal performance. LTE is an enhanced technology which is developed by 3GPP to support the needs of consumers that has improved the previous technologies. This research proposes the network planning LTE TDD duplexing technique using a frequency of 2300 MHz in the city of Pekanbaru, Riau, with the bandwidth of 10 MHz and 15 MHz, respectively. The network design and simulation was done by radio planning software Atoll v3.1.2. In the design simulation such parameters are measured i.e. coverage dimensioning simulation with signal level prediction. The results shows the signal level coverage including 512 sites with bandwidth of 10 MHz and 351 sites with bandwidth of 15 MHz, respectively.Keywords : LTE, TDD, Bandwidth, Coverage planning, Atoll